Diagnostic and Prognostic Significance of Methionine Uptake and Methionine Positron Emission Tomography Imaging in Gliomas - Palanichamy, Kamalakannan; Chakravarti, Arnab (Frontiers in Oncology, 2017)
The present most common image diagnostic tracer in clinical practice for glioma is 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) for brain tumors diagnosis and prognosis. PET is a promising molecular imaging technique, which provides real-time information on the metabolic behavior of the tracer. The diffusive nature of glioblastoma (GBM) and heterogeneity often make the radiographic detection by FDG-PET inaccurate, and there is no gold standard. FDG-PET often leads to several controversies in making clinical decisions due to their uptake by normal surrounding tissues, and pose a challenge in delineating treatment-induced necrosis, edema, inflammation, and pseudoprogression. Thus, it is imperative to find new criteria independent of conventional morphological diagnosis to demarcate normal and tumor tissues. We have provided proof of concept studies for 11C Methionine-PET (MET-PET) imaging of gliomas, along with prognostic and diagnostic significance. MET-PET is not widely used in the United States, though clinical trials from Japan and Germany suggesting the diagnostic ability of MET-PET imaging is superior to FDG-PET imaging for brain tumors. A major impediment is the availability of the onsite cyclotron and isotopic carbon chemistry facilities. In this article, we have provided the scientific rationale and advantages of the use of MET-PET as GBM tracers. We extend our discussion on the expected pitfalls of using MET-PET and ways to overcome them by incorporating a translational component of profiling gene status in the methionine metabolic pathway. This translational correlative component to the MET-PET clinical trials can lead to a better understanding of the existing controversies and can enhance our knowledge for future randomization of GBM patients based on their tumor gene signatures to achieve better prognosis and treatment outcome.